Gift of Independence: 30 Years of Reforms, Achievements, and Results in the Field of Accounting and Auditing in Uzbekistan - PhD, Erkin Temirovich Shodiev; Nigora Yusupovna Rasulova (Periodica Journal, 2023)
This article examines the historical and modern development of the theoretical and methodological foundations of accounting and auditing in the Republic of Uzbekistan after the establishment of independence. It summarizes the current state of accounting standards and practices in Uzbekistan, discusses how the regulatory environment in Uzbekistan has shaped the development of accounting and auditing regulations, and identifies significant challenges remaining in the efforts to move accounting and financial reporting in Uzbekistan into greater coherence with international standards. Contributions to the professional literature from this article include illustrating the factors affecting the pace of change in a former Soviet Block country and identifying current obstacles remaining to the successful completion of the convergence of Uzbekistan national accounting and auditing standards with international standards, including needs for more complete development of an infrastructure supporting management accounting and internal auditing in addition to additional support for traditional financial accounting and auditing qualifications.
Keywords: national accounting; standards; national auditing standards